Long-term alterations of collagen reconstruction and basement membrane regeneration after corneal full-thickness penetrating injury in rabbits - Jingjing Chen; Yuqing Luo; Luting Xie; Na Meng; Sumei Li; Shifang Xiao; Xia Li (PLoS ONE, 2025)
Purpose To investigate the long-term alterations of collagen reconstruction and basement membrane (BM) regeneration after corneal full-thickness penetrating injury in rabbits. Methods The corneal full-thickness penetrating injury model was established in the left eye of New Zealand White rabbits using a 2.0 mm trephine. All corneas were evaluated using slit-lamp photography, hematoxylin and eosin staining, immunofluorescent staining for collagen types I and III (Col I, III), and transmission electron microscopy for collagen fibers and basement membrane. Results Between 3 days and 3 weeks, Col I and III expression were documented, exhibiting a largely disorganized distribution throughout the stromal thickness. At 3 weeks, the epithelial basement membrane (EBM) partially regenerated. From 3 weeks to 2 months, Col III was undetectable in the anterior stroma but present in the posterior stroma; Col I was disorganized in the posterior stroma. At 2 months, Descemet’s membrane (DM) exhibited incomplete regeneration. From 3 to 4 months, Col I was disorganized in only a small part of the posterior stroma; Col III persisted in the posterior stroma; the EBM fully regenerated while DM exhibited incomplete regeneration. Conclusions Following full-thickness corneal injury, persistent fibrosis within the posterior stroma appears to be primarily responsible for the persistence of corneal scarring. Notably, regeneration of the EBM coincides with remodeling of the anterior stroma, whereas incomplete regeneration of DM is associated with posterior stromal fibrosis.